Hubungan Kepatuhan Hemodialisis Dengan Disfungsi Ereksi Pada Pria Usia Subur Di RSUD Ungaran - Sujana, Treesia; Kadoyu, Miktam Herdianto; Dary, Dary - (Jurnal Keperawatan Muhammadiyah, 2020)
Abstract Background Hemodialysis is a program that replaces the function of the kidneys due to damage to the kidney organs (dialysis), where patients with chronic kidney failure must obedient in undergoing hemodialysis. Disobedience can cause therapy failure. Prolonged hemodialysis programs have an impact on reproductive health. It often happens, patients who undergo hemodialysis program have erectile dysfunction problems where patients who do hemodialysis will experience decreased libido, impotencei, infertility, gynecomastia. The purpose of this study was to determine the relationship between adherence to undergo hemodialysis therapy with erectile dysfunction in men of childbearing age who have chronic kidney failure. The research method used in this study is a quantitative correlation research method with a cross-sectional approach, with  questionnairs as the data collection tool. The sample used in this study was determined by purposive sampling with 31 respondents of childbearing age undergoing hemodialysis. Data analysis used are descriptive analysis and bivariate test and chi-square correlation test. The resultsof this study are participants that compliance with hemodialysis in the obedient category are 30 people (97%) and erectile dysfunction in men of childbearing age in the category of erectile dysfunction are 27 people (87%). Chi-square correlation test results obtained Value = 0.573 which means greater than alpha 0.05 (0.573> 0.05) then the Ha hypothesis is rejected and Ho is accepted so it can be concluded that there is no significant relationship between adherence to undergoing hemodialysis therapy with erectile dysfunction in men of childbearing age at Ungaran District Hospital. Compliance, Erectile Dysfunction, Hemodialysis, Productive  men